Hα emission objects in Circinus. Issue 3 (1st March 2013) - Noroozi, S.; Haas, M.; Chen, Z.; Chini, R.
Abstract We present a new survey for Hα emission objects in the Circinus cloud complex and introduce an efficient photometric method for detecting Hα emission via observations in a narrow‐band filter. The observed flux is compared to a blackbody fit of the continuum. Our search strategy reveals 20 stars with strong Hα emission (EW > 10 Å), eight of them being new detections. All Hα stars display infrared excess corroborating their youth. On the other hand, the region contains a number of infrared excess objects that do not show Hα emission. Our results support the picture that accretion – as witnessed by Hα emission – is a highly variable phenomenon. Therefore, Hα surveys can only trace the temporarily active objects. In contrast, infrared excess is a more robust tracer that reveals most of the population of young stellar objects in a star forming region. Our analysis of the general stellar content of the region yields a reliable distance of 450 pc for the Circinus cloud. Moreover, we find a ratio of total‐to‐selective extinction of RV = 2.8 suggesting that smaller‐than‐normal dust grains may be present. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)